The most dangerous game = [Malvado Zaroff] - Schoedsack, Ernest B., 1893-1979; Pichel, Irving, 1891-1954; Creelman, James Ashmore; McCrea, Joel, 1905-1990; Connell, Richard Edward, 1893-1949.; RKO Radio Pictures; Cinetel Films ([Culver City, CA] : RKO Radio Pictures, Inc., 1932)
A madman on his island fortress, tired of pursuing game, becomes obsessed with the idea of hunting the most dangerous game of all-- man.
Originally released as a motion picture in 1932.
Based on a story by Richard Connell.
Joel McCrea, Fay Wray, Leslie Banks, Robert Armstrong, Noble Johnson, Steve Clemento, Dutch Hendrian.
Cinematographer, Henry Gerrard; editor, Archie F. Marshek; music, Max Steiner.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Big game hunting -- Drama; Castaways -- Drama; Aristocracy (Social class) -- Russia -- Drama; Feature films; Action and adventure films; Fiction films; Film adaptations; Thrillers (Motion pictures); Internet videos; Streaming video